The Effect of Religious Programs on Increasing Religious Awareness and Social Concerns of Students in Madrasah Aliyah Bandung - Adrian, Syntia; Supriadi, Udin; Anwar, Saepul (Program Studi Pendidikan Agama Islam, 2023)
Higher education institutions have a heavy task in carrying out the educational mandate, as they must be able to realize a unity between the knowledge, personality, and skills of students in carrying out religion in society. This study, thus, aims to determine the influence of students' religious experiences in schools on increasing their religious awareness and social concerns. This research employed a descriptive quantitative method with a correlation design. The research instrument was in the form of a questionnaire, with data analysis techniques using descriptive statistics and inference statistics. The results uncovered that students' religious experiences at school exerted a significant influence both on students' religious awareness, with a correlation value of 0.658 and on students' social concern, with a correlation value of 0.590. Students' religious experience at school had an influence of 43.29% on students' religious awareness and 34.8% on students' social concerns.